Donor lymphocyte infusion combined with azacitidine after allogeneic HSCT in pediatric AML: a single-center retrospective analysis - Bica, Ana Maria; Marcu, Andra Daniela; Jercan, Cristina Georgiana; Iordan, Iuliana; Serbanica, Andreea Nicoleta; Avramescu, Irina; Colita, Matei; Popa, Delia Codruta; Constantinescu, Ileana; Ichim, Alexandra Mihaela; Colita, Andrei; Colita, Anca (Frontiers in Pharmacology, 2026)
IntroductionDonor lymphocyte infusion (DLI) can enhance graft-versus-leukemia (GvL) effects following allogeneic hematopoietic stem cell transplantation (HSCT) in pediatric acute myeloid leukemia (AML). However, the optimal integration of azacitidine (Aza) with DLI in children remains uncertain.MethodsWe retrospectively analyzed 16 pediatric AML patients (≤18 years) treated at Fundeni Clinical Institute between 2016 and 2024 who received DLI in combination with azacitidine (75 mg/m2/day for 7 days every 4 weeks) after HSCT. DLI was administered prophylactically or preemptively based on mixed donor chimerism (MDC), measurable residual disease (MRD) positivity, or high-risk cytogenetics, or therapeutically for post-transplant relapse, with or without chemotherapy. Outcomes assessed included overall survival (OS), donor chimerism, relapse rate, and graft-versus-host disease (GVHD).ResultsAfter a median follow-up of 46.5 months, five patients received prophylactic/preemptive DLI and eleven received therapeutic DLI (seven with chemotherapy, four without). All patients in the prophylactic/preemptive group achieved full donor chimerism and MRD negativity, with an OS of 80% at 2.7 years. In the therapeutic group, median OS was 23.8 months with chemotherapy and 13.8 months without. OS differences between groups were not statistically significant (p = 0.384). Acute GVHD occurred in two patients (12.5%) in the therapeutic + chemotherapy subgroup; no chronic GVHD or non-relapse mortality was observed.ConclusionAzacitidine combined with DLI is feasible and safe in pediatric AML after HSCT, particularly when applied prophylactically or preemptively to restore donor chimerism or eradicate MRD. Therapeutic use in overt relapse remains challenging and provides limited benefit. Prospective multicenter studies are needed to define optimal timing, dosing, and combination strategies for integrating azacitidine with DLI in this high-risk pediatric population.